Analysis and prediction of glacier evolution trend (2020–2100) in Northern Xinjiang - Xi-yong Sun; Yang Jiao; Qian-li Ma; Jing-hui Fan; Xiao-min Du; Jia-feng Liu; Shao-qiang Wang; Wen-chen Hu (China Geology, 2024)
ABSTRACT: Glaciers, as “solid reservoirs”, are precious resources in arid areas. The study of glaciers is of great significance to the sustainable development and management of agriculture and the economy in northern Xinjiang. The area of glacier distribution on the 1963 topographic map data, 1975 MSS data, 2000 ETM data, 2008 CBERS-2 data, 2014 and 2018 ETM+ were collected as secondary data. According to the remote sensing survey, the glacier areas in Northern Xinjiang are identified during 1963–2018. Based on the evolution of glacier area in the past 55 years, and using two scenarios, the average annual decrease area of a region during the whole 1963–2018 and the period with the minimum reduction area, the glacier areas of Southern Tianshan Mountains, Western Tianshan Mountains, Eastern Tianshan Mountains, the Sawuer Mountains and Altai Mountains in Northern Xinjiang, and the whole northern Xinjiang in 2030, 2040, 2050, and 2100 are examined and predicted. In 2100, the glacier area in Northern Xinjiang may decrease by 43%–59%.